2021
DOI: 10.1021/acs.orglett.1c00148
|View full text |Cite
|
Sign up to set email alerts
|

Modular Domino Process toward Highly Functionalized Pyrroles via Pd-Catalyzed [4 + 1] Annulation under Mild Conditions

Abstract: A Pd-catalyzed decarboxylative approach for the modular synthesis of highly functionalized pyrroles is presented. This protocol utilizes readily available cyclic carbonates and amines as reaction partners and only generates CO2 and H2O as byproducts. This methodology could be operated at room temperature and open to air, thus serving as an ideal means for the derivatization of bioactive compounds. Mechanism investigations suggested that the stereoselective formation of the (Z)-configured γ-amino ketone interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 54 publications
1
19
1
Order By: Relevance
“…After that, Guo and coworkers developed an efficient method for the synthesis of polysubstituted pyrroles via decarboxylative [4+1] annulation of cyclic carbonates 183 with primary amines 187 (Scheme 90). [64b] This protocol exhibited excellent substrate scope and quite wide functional group tolerance. Especially, this method could be successfully applied to aliphatic amines, delivering the desired pyrrole products 188 , despite the fact that the nucleophilic attack to the carbonyl of the cyclic carbonate by aliphatic amine would conveniently occur to generate the byproduct carbamate.…”
Section: π‐Allyl Palladium Bearing C‐nucleophilementioning
confidence: 96%
“…After that, Guo and coworkers developed an efficient method for the synthesis of polysubstituted pyrroles via decarboxylative [4+1] annulation of cyclic carbonates 183 with primary amines 187 (Scheme 90). [64b] This protocol exhibited excellent substrate scope and quite wide functional group tolerance. Especially, this method could be successfully applied to aliphatic amines, delivering the desired pyrrole products 188 , despite the fact that the nucleophilic attack to the carbonyl of the cyclic carbonate by aliphatic amine would conveniently occur to generate the byproduct carbamate.…”
Section: π‐Allyl Palladium Bearing C‐nucleophilementioning
confidence: 96%
“…For instance, the stereoselective amination of intermediate T1 gives rise to -amino ketones with a (Z)-configuration that undergo subsequent intramolecular nucleophilic cyclization to form pyrroles (Scheme 4a, path a). 18 The structure of the pyrrole products can be smoothly modulated by changing the substituents on the vinyl cyclic carbonate A. This protocol is feasible for both aryl and alkyl amine nucleophiles.…”
Section: Nucleophilic Capture Of Zwitterionic Metal (Palladium or Copper) Enolates Or Their Equivalentsmentioning
confidence: 99%
“…Our group recently reported a Pd-catalyzed decarboxylation process that enabled the [4+1] annulation of VMCCs with amines as reaction partners toward the generation of pyrroles (Scheme 18). 27 It is worth mentioning that this methodology could be utilized for the synthesis of a number of tetra-and pentasubstituted pyrroles, which are synthetically challenging. Control experiments indicated that the reaction proceeded via an intermediate Z-configured -amino unsaturated ketone.…”
Section: Short Review Synthesismentioning
confidence: 99%